Significance of Anti-HLA Antibodies on Adult and Pediatric Heart Allograft Outcomes - Mangiola, Massimo; Marrari, Marilyn; Feingold, Brian; Zeevi, Adriana (Frontiers in Immunology, 2017)
As methods for HLA antibody detection have evolved and newer solid phase assays are much more sensitive, the last 15 years has seen a renewed focus on the importance of HLA antibodies in solid organ transplant rejection. However there is still much controversy regarding the clinical significance of antibody level as depicted by the mean fluorescence intensity (MFI) of a patient’s neat serum. Emerging techniques, including those that identify antibody level and function, show promise for the detection of individuals at risk of allograft rejection, determination of the effectiveness of desensitization prior to transplant, and for monitoring treatment of rejection. Here we review current publications regarding the relevance of donor-specific HLA antibodies in adult and pediatric heart transplantation with graft survival, development of antibody mediated rejection and cardiac allograft vasculopathy. The negative impact of DSA on patient and allograft survival is evident in adult and pediatric HT recipients. Many questions remain regarding the most appropriate frequency of assessment of pre- and post-transplant DSA as well as the phenotype of DSA memory vs. true de novo antibody using large multi-center adult and pediatric cohorts and state-of-the-art methodologies for DSA detection and characterization.